FEATURES OF FEEDING YOUNG CHILDREN AS A RISK FACTOR FOR THE DEVELOPMENT OF DENTAL CARIES - Хамидов Д. С.; Холмуминов Н. Н. (Modern American Journals, 2026)
The article presents the results of a study of the prevalence and intensity of dental caries in young children depending on the nature and mode of feeding. 800 children aged 6 to 36 months were examined. The analysis of the effect of breastfeeding and artificial feeding, the frequency of night feedings, the use of bottles, as well as the consumption of sugar-containing products on the development of the carious process was carried out. It has been established that violation of the feeding regimen, prolonged breastfeeding after 12 months, frequent night feedings and the use of sweets reliably increase the intensity of dental caries. The data obtained confirm the need for early prevention and informing parents about the principles of rational feeding of young children in order to prevent caries.
Keywords: Young children; dental caries; breastfeeding; artificial feeding; diet; night feedings; sugar-containing products; prevention of caries.